2005
DOI: 10.1017/s1461145705005523
|View full text |Cite
|
Sign up to set email alerts
|

A possible association between the [minus sign]116C/G single nucleotide polymorphism of the XBP1 gene and lithium prophylaxis in bipolar disorder

Abstract: Bipolar disorder (BPD) is a severe, chronic, and life-threatening illness, and its pathogenesis remains unclear. Recently, a functional polymorphism (-116C/G) of the X-box binding protein 1 (XBP1) gene was reported to be a genetic risk factor for BPD. Moreover, the endoplasmic reticulum stress responses were impaired in cultured lymphocytes from BPD patients with the -116G allele and only valproate rescued such impairment among three major mood stabilizers. In this context, we hypothesized that BPD patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…The period of observation was 2 years. The same lack of association was found in the same year by Masui et al [59] in a sample of 83 bipolar I and 78 bipolar II patients, all of Japanese origins. The period of observation was 1 year in that case.…”
Section: Challenging the Chronic Molecular Events: Results From Pharmsupporting
confidence: 81%
“…The period of observation was 2 years. The same lack of association was found in the same year by Masui et al [59] in a sample of 83 bipolar I and 78 bipolar II patients, all of Japanese origins. The period of observation was 1 year in that case.…”
Section: Challenging the Chronic Molecular Events: Results From Pharmsupporting
confidence: 81%
“…Pharmacogenomic studies that aimed to identify genetic variants associated with lithium treatment responses, efficacy, tolerability, and safety in patients with BPD have identified novel SNPs located in protein coding genes. Candidate gene studies have reported several polymorphisms associated with lithium treatment response located in the 5-HTT [101,102], [74], and CACNG2 [103] genes (see Table 2). …”
Section: Lithium Treatment For Bipolar Disordermentioning
confidence: 99%
“…Encodes a protein that catalyzes the decarboxylation of aspartate, cysteine sulfinic acid, and cysteic acid to beta-alanine, hypotaurine, and taurine, respectively [74,90] Two linked SNPs, rs17026688 and rs17026651 mapped to GADL1 gene showed associations with lithium response in patients with BPD [17] pharmacogenomics studies of mood disorders are described below. They can be considered as future opportunities for pharmacogenomic studies in mood disorders.…”
Section: Inositol Polyphosphate-1--phosphatasementioning
confidence: 99%
“…-116C>G NA 66 Japanese [Masui, et al 2005] Significant mtDNA 10398A>G rs2853826 54 Japanese [Washizuka, et al 2003]…”
Section: Tph1mentioning
confidence: 99%